2017
DOI: 10.1159/000471877
|View full text |Cite
|
Sign up to set email alerts
|

Changing Epidemiological Patterns in Traumatic Brain Injury: A Longitudinal Hospital-Based Study in Belgium

Abstract: Background: Various reports have suggested that epidemiological patterns of Traumatic Brain Injury (TBI) are changing in high-income countries, but the evidence to support this is often indirect and only a few longitudinal studies exist. We aimed to explore epidemiological patterns of TBI in Belgium over a 10-year period. Methods: A retrospective analysis of Minimum Hospital Data provided by Statistics Belgium was performed for the period 2003-2012. ICD-9 classification was used to identify TBI and to differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 23 publications
8
27
1
Order By: Relevance
“…The main cause of trauma in all elderly age groups was fall (Table 1 ), which is in accordance with our earlier findings [ 22 , 28 ] as well as with the results of many other studies [ 8 , 15 , 17 , 19 , 23 , 34 , 36 , 40 ]. Although there was a predominant injury mechanism, there was a notable significant difference between the age groups regarding several other characteristics (Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…The main cause of trauma in all elderly age groups was fall (Table 1 ), which is in accordance with our earlier findings [ 22 , 28 ] as well as with the results of many other studies [ 8 , 15 , 17 , 19 , 23 , 34 , 36 , 40 ]. Although there was a predominant injury mechanism, there was a notable significant difference between the age groups regarding several other characteristics (Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…The high incidence of TBI-associated disability and death incurs many costs and social challenges [5]. In the United States, the cost of TBI has been estimated to be greater than USD 75 billion per year, and the cost for one patient in their whole lifetime is estimated at USD 396,000 [6]. Indeed, even after emergency treatment and hospitalization, deficits persist, even in cases of mild TBI.…”
Section: Impactmentioning
confidence: 99%
“…In the current issue of Neuroepidemiology , Peeters et al [2] present the findings of a longitudinal study of hospital admissions for TBI over a 10-year period in Belgium. The study identified that contrary to findings in the United States, TBI hospital admissions in young to middle aged adults have decreased over time.…”
mentioning
confidence: 99%
“…As discharges from the emergency department did not appear to be included in the analysis by Peeters et al [2], it remains unclear if the trends observed in the United States are also occurring in Europe. Indeed, while the authors state that there was no change in hospital policy during the study period, there may be an increasing trend in clinical practice to discharge rather than admit people to hospital following a TBI, particularly if the reason for admission was solely for the purpose of monitoring the person's condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation